Building Nano-Knowledge for Sustainable Lagoon Water Resources Governance - Amu-Mensah, Marian A.; Agyeman, Martha Duku; Addico, Gloria; Chrisk, Mario E.; Martey, Michael; Nortey, Gertrude; Amedorme, Bright; Nelson, Kingsley; Hodgson, Isaac; Nyave, Samuel Asiamah (Building Nano-Knowledge for Sustainable Lagoon Water Resources Governance, 2025)
Water is more than a resource, it is a lifeline, deeply embedded in the social, cultural, and ecological fabric of communities. Local nano-knowledge, particularly the observations of those who regularly interact with water bodies, plays a crucial role in identifying early signs of contamination and ecological shifts. Subtle changes in water colour, odour, and taste, as well as fluctuations in aquatic biodiversity, can serve as key indicators of environmental stress long before scientific instruments detect measurable changes. This book explores the integration of traditional nano-knowledge with cutting-edge scientific advancements, particularly nano-sensors, to create a more holistic and responsive water monitoring system. It introduces the concept of "nano-knowledge", small but vital units of environmental intelligence gathered through lived experience, and examines how these insights, when validated and incorporated into governance frameworks, can strengthen water stewardship and resilience. It is important to note that the smallest details often carry the loudest warnings. Recognizing changes in water colour, smell, or microscopic life is not just scientific, it is spiritual, cultural, and political association. These “nano” insights form the heartbeat of resilient, inclusive, and effective water governance. Drawing from an extensive study conducted across four coastal lagoon communities in Accra, Ghana in West Africa, this work highlights the factors contributing to water quality degradation and ecosystem imbalance. Using a combination of field data, community perspectives, and policy analysis, the research reveals critical gaps in water management strategies, especially the disconnect between policymaking and nano-knowledge of scientific and grassroots conservation efforts. Findings indicate that parameters such as salinity, dissolved oxygen, and bacterial contamination exceed safe limits, leading to biodiversity loss and ecological stress. These challenges underscore the urgency of integrating nano localized environmental awareness with scientific methodologies to inform adaptive and sustainable policies. By bridging traditional ecological nano-knowledge with nano modern water assessment tools, this book advocates for a participatory governance model that values both empirical data and community-driven conservation practices. Effective policies must not only be scientifically sound but also culturally embraced and locally implemented. Recognizing the intricate connections between water quality, biodiversity, and socio-economic stability, this work calls for a paradigm shift toward inclusive and intricate evidence-based water governance. In conclusion, water governance is not solely a technical issue but a multidimensional challenge that intersects with cultural heritage, economic priorities, and ecological sustainability. By fostering collaboration between policymakers, researchers, and local stewards, we can develop resilient water governance systems that safeguard vital aquatic ecosystems for future generations.